Purifying Selection in Corvids Is Less Efficient on Islands - Kutschera, Verena E (Mol Biol Evol, 2020)
Theory predicts that deleterious mutations accumulate more readily in small populations. As a consequence, mutation load is expected to be elevated in species where life-history strategies and geographic or historical contingencies reduce the number of reproducing individuals. Yet, few studies have empirically tested this prediction using genome-wide data in a comparative framework. We collected whole-genome sequencing data for 147 individuals across seven crow species (Corvus spp.). For each species, we estimated the distribution of fitness effects of deleterious mutations and compared it with proxies of the effective population size N(e). Island species with comparatively smaller geographic range sizes had a significantly increased mutation load. These results support the view that small populations have an elevated risk of mutational meltdown, which may contribute to the higher extinction rates observed in island species.